The Koebner Phenomenon and First Episode of Psoriasis after Contact with Cold Metal in Fitzpatrick Type II Skin - Kadam, Priya; Aneela, Irrum (Biology, Engineering, Medicine and Science Reports, 2026)
A female in her thirties with Fitzpatrick skin type II and a childhood history of atopic dermatitis presented with a first episode of psoriasiform plaques following localized trauma from contact with cold metal. Within 72 hr, the initially painful erythematous eruption evolved into well-demarcated, raised, scaly plaques consistent with plaque psoriasis morphology. The patient self-initiated symptomatic cooling with aloe vera gel prior to community medical assessment, after which she was treated with emollients and a low-potency topical corticosteroid (1% hydrocortisone), resulting in good clinical response. This presentation is suggestive of a Koebner phenomenon, whereby cutaneous trauma precipitates psoriatic lesions at sites of injury. However, the diagnosis remains uncertain given the absence of a prior personal history of psoriasis, raising the possibility that this episode represents the initial manifestation of latent disease rather than true Koebnerisation. Subsequently, the patient experienced recurrent plaque psoriasis episodes temporally associated with psychosocial stressors. The Koebner phenomenon has been variably reported across skin phototypes, with limited data in Asian populations; some studies describe post-inflammatory hypopigmentation following lesional resolution in darker skin types. In this case, transient pigmentary change was also observed following lesion resolution. This case highlights the diagnostic challenge in distinguishing trauma-induced Koebner response from first presentation of plaque psoriasis and underscores the potential role of physical injury and psychological stress as precipitating factors in susceptible individuals.
Keywords: Koebner Effect; Psoriasis; Steroid; Topical; Trauma